Effect of ukhuwwah driven social cohesiveness in governing quality innovation for sustainable development goals - Mhd. Sarif, Suhaimi (International Journal of Business, Economics and Law - IJBEL, 2019)
Social cohesiveness enables organizations to respond the dynamism of the environment through the strength of the human resources, capability and intellectualism so that organizations continue to sustain competitive advantage and performance. The existing practice of social cohesiveness in organizations is through strategic cooperation, bonding among workers, and socialization without much emphasized on spirituality and soul enhancement. Islamic approach to social cohesiveness is through ta’awun and ukhuwwah. While ta’awun denotes strategic cooperation among members of organizations and stakeholders, ukhuwwah manifests strategic bonding (ukhuwwah). When ukhuwwah drives social cohesiveness, it is also in the business of governing quality innovation for sustainable development goals. Thus, ukhuwwah enables cohesiveness among innovation workers in ensuring the governance of quality innovation. In the rigid rules and procedures situation, which is essential, ukhuwwah reinforces qualitatively with soul, spirituality and consciousness. Social equity theory deliberates the weight of the rewards. Thus, this study aims to explore the effect of ukhuwwah in governing quality innovation for sustainable development goals, specifically in Malaysia. This study uses personal interview with 10 innovation workers in Malaysia. The feedback from the informants argued that ukhuwwah combines cohesiveness and weight of rewards to sustain development goals with more governance and innovation framework. Future studies should use case study method to deliberate the proposition in more integrated, comprehensive and rigorous.